Substitution of mulberry leaf meal on feed intake, body weight and carcass characteristics of Tigray highland lambs - Gebrekidan Tesfay; Berhan Tamir; G. Berhane (Indonesian Center for Animal Research and Development (ICARD), 2018)
The purpose of this study is to evaluate effects of partial or full substitution of mulberry leaf meal for concentrate mix on performances of Tigray highland lambs. Thirty intact yearlings Tigray highland male lambs (average initial body weights of 17.8±0.95 kg) were separated into 6 groups based on their live weight with each groups assigned 5 treatment diets (RCBD), that are: T1: 300 g concentrate mix alone, T2: 225 g concentrate mix + 86.55 g mulberry leaf, T3: 150 g concentrate mix + 173.1 g mulberry leaf, T4: 75 g concentrate mix + 259.7 g mulberry leaf and T5: 346.2 g mulberry leaf alone. The treatments diets were designed in such a way that concentrate mix was progressively replaced by mulberry leaf meal from 0% to 100% at iso-nitrogenous level. Lambs were adapted to experimental diets for 15 days, and after adaptation period, feeding trial was conducted. Results reveal that complete substitution of concentrate mix by mulberry leaf meal showed in higher (P<0.05) total dry matter, organic matter, NDF and ADF intake than the sole concentrate mix. The growth performance parameters resulted comparable across all the treatment diets. The slaughter weight and empty weight resulted higher (P<0.05) in sole mulberry leaf meal as compared to the whole concentrate mix supplemented lambs. On the other hand, the dressing percentage on empty body weight base and hot carcass weight showed less difference (P>0.05) across the different treatments. Therefore, mulberry foliage could potentially be used to replace concentrate mix as a feed supplement for the small holder farmers in Ethiopia.